Lead structures for Applications in Photodynamic Therapy. 2. Synthetic studies for photo-triggered release systems of bioconjugate porphyrin photosensitizers - SENGE, MATHIAS (My University, 2009)
Photodynamic therapy (PDT) selectivity and specificity can be improved by binding the photosensitizers to target receptors. One approach is to cross-link porphyrins to a biological target receptor via the photocleavable o-nitrobenzyl linker, where a controlled released of the porphyrin can be monitored upon irradiation. The synthetic pathways involved esterification of a porphyrin-carboxylic acid and a unit containing the o-nitrobenzyl alcohol moiety and the bioconjugate. Reactions of a model porphyrin and o-nitrobenzyl alcohol using the carbonyl activating carbodiimide reagent DCC gave a stable N-acyl urea porphyrin, whereas use of EDAC (1-ethyl-3-(3-dimethyl aminopropyl)carbodiimide hydrochloride) gave the desired compounds. Further studies were carried out on the attachment of carbohydrates (i.e. potentially receptor binding ligands) through such a linker to porphyrins. Preliminary irradiation experiments of such a compound show that upon UV irradiation (350 nm) for 80 min, approximately 50% of the porphyrin was cleaved to release the carboxylic acid porphyrin photosensitizer indicating the utility of such systems as photosensitizers delivery systems.
PUBLISHED
Keywords: Chemistry